Intravenous sildenafil citrate and post-cardiac surgery acute kidney injury: a double-blind, randomised, placebo-controlled trial. (June 2020) - Kumar, Tracy; Aujla, Hardeep; Woźniak, Marcin; Dott, Will; Sullo, Nikol; Joel-David, Lathishia; Pais, Paolo; Smallwood, Dawn; Miller, Douglas; Eagle-Hemming, Bryony; Di Paola, Ana Suazo; Barber, Shaun; et al.
Abstract: Background: This study assessed whether i.v. sildenafil citrate prevented acute kidney injury in at-risk patients undergoing cardiac surgery with cardiopulmonary bypass. Methods: In a double-blind RCT, adults at increased risk of acute kidney injury undergoing cardiac surgery in a single UK tertiary centre were randomised to receive sildenafil citrate 12.5 mg kg −1 i.v. over 150 min or dextrose 5% at the commencement of surgery. The primary outcome was serum creatinine measured at six post-randomisation time points. The primary analysis used a linear mixed-effects model adjusted for the stratification variables, baseline estimated glomerular filtration rate, and surgical procedure. Secondary outcomes considered clinical events and potential disease mechanisms. Effect estimates were expressed as mean differences (MDs) or odds ratios with 95% confidence intervals. Results: The analysis population comprised eligible randomised patients that underwent valve surgery or combined coronary artery bypass graft and valve surgery, with cardiopulmonary bypass, between May 2015 and June 2018. There were 60 subjects in the sildenafil group and 69 in the placebo control group. The difference between groups in creatinine concentration was not statistically significant (MD: 0.88 μmol L −1 [–5.82, 7.59]). There was a statistically significant increase in multiple organ dysfunction scores in the sildenafil group (MD: 0.54 [0.02, 1.07]; P =0.044). Secondary outcomes, and biomarkers of kidney injury, endothelial function, and inflammatory cell activation, were not significantly different between the groups. Conclusions: These results do not support the use of i.v. sildenafil citrate for kidney protection in adult cardiac surgery. Clinical trial registration: ISRCTN18386427.